Colorblind Racism - Part 1 - Anna Hackman (2018)
Capsule vidéo qui explique le racisme aveugle à la race, premier partie.
Keywords: approches et analyses; cours; discipline; intersectionnalité; pol5480; premier cycle; racisme; sciences humaines; sociologie; systèmes d'oppressions; thématiques; violences

Colorblind Racism - Part 2 - Anna Hackman (2018)
Capsule vidéo qui explique le racisme aveugle à la race, deuxième partie.
Keywords: approches et analyses; cours; discipline; intersectionnalité; pol5480; premier cycle; racisme; sciences humaines; sociologie; systèmes d'oppressions; thématiques; violences

Affect as methodology: Feminism and the politics of emotion - Åhäll, Linda (International Political Sociology, 2018)
International relations scholars are increasingly paying attention to “the emotional” as a way to understand global politics. What is often missing from these conversations is feminist knowledge on affect, and also discussions about methodology. By presenting a feminist methodological approach to the affective-discursive to analyze the politics of emotion, this paper aims to fill this gap. It starts by discussing feminist critiques of the “affective turn.” Then, a methodological framework of gender, discourse, and affect as a structure that “goes-without-saying” is presented. Hemmings’ concept of affective dissonance is used as a tool guiding a feminist curiosity, useful to zoom in on the political puzzle of what emotion (in its broadest sense) does. The third section draws on two examples of being emotional about violent “Woman” to illustrate how moments of affective dissonance spark a feminist curiosity about gender, agency, and political violence. In conclusion, the paper argues that feminist knowledge on affect offers a way to re-tune, reset, and reimagine research on the politics of emotion. By prioritizing affect as methodology, feminist knowledge should be valuable for critical endeavors interested in changing the status quo, no matter if the political puzzle is about gender or not.
Keywords: corps; discipline; genre; histoire et politique; méthodologie; relations internationales; ressource en ligne; science politique; science politique et droit; sciences humaines; sociologie; thématiques; violences; émotions

Masculinisme et violences contre les femmes : une analyse des effets du contremouvement antiféministe sur le mouvement féministe québécois - Blais, Mélissa (Université du Québec à Montréal, 2018)
Cette thèse de doctorat traite des effets des stratégies et tactiques antiféministes sur les féministes québécoises œuvrant dans le secteur de la prévention et de la lutte contre les violences envers les femmes. J'y étaye l'hypothèse selon laquelle le contremouvement antiféministe force le mouvement féministe à adapter ses choix organisationnels, ses modes d'action et ses discours, au détriment de ses intérêts premiers. Cette recherche qualitative prend appui sur un corpus de 87 entretiens semi-dirigés menés entre 2006 et 2015 auprès de féministes à travers le Québec. Elle emprunte à l'épistémologie féministe une démarche d'enquête qui « interprète » au lieu de « valider » la perception des participantes à la recherche des conséquences qu'occasionne le contremouvement sur leur communauté, leurs organisations et elles-mêmes. Son originalité tient également au fait qu'elle promeut un cadre théorique qui permet de couvrir non seulement les dimensions micro et mésosociologiques de l'analyse, mais aussi macrosociologiques. En effet, les niveaux micro et mésosociologiques sont le plus souvent examinés à l'aide des propositions théoriques voulant que le contremouvement imite les pratiques du mouvement et que les interactions entre un mouvement et son contremouvement évoluent en fonction des coups qu'ils se portent. La dimension macrosociologique du conflit, soit les rapports sociaux de sexe, est quant à elle considérée à l'aide de la théorie du sexage de Colette Guillaumin qui réitère la présence des antagonismes sociaux qui opposent les femmes féministes aux hommes antiféministes. Dans l'ensemble, cette thèse présente les formes d'antiféminismes allant des moins organisées (antiféminisme ordinaire et antiféminisme anticapitaliste) aux plus organisées (l'antiféminisme religieux et conservateur ainsi que le masculinisme), pour ne retenir que le masculinisme comme communauté du contremouvement à l'origine des effets documentés. En discutant des phases de développement du masculinisme selon les avancées du mouvement féministe, elle souligne le caractère pernicieux des tactiques masculinistes mises de l'avant depuis son entrée dans sa phase d'institutionnalisation en 2010. En outre, elle démontre que les stratégies et tactiques masculinistes identifiées ont des conséquences d'ordre politique, c'est-à-dire qu'elles affectent la capacité du mouvement à transformer les rapports sociaux, à influencer les politiques publiques et à obtenir des ressources financières et matérielles. Le masculinisme produit aussi des effets organisationnels chez les féministes, que révèlent les ajustements du travail d'intervention, les modifications du répertoire tactique, les transformations des mandats organisationnels ainsi que les nouvelles divisions entre les féministes sur la question de la place des hommes dans le mouvement. Face au discours masculiniste de la symétrie de la violence et de la « crise » de la masculinité, l'enquête dévoile aussi des effets discursifs du masculinisme sur le travail de signification des violences faites aux femmes, de sorte que les féministes ont tendance à reléguer leur fondement sociologique au second plan. Enfin, les effets biographiques sont perceptibles à travers un engagement plus distancié des féministes qui cherchent notamment à se protéger des conséquences du masculinisme sur leur santé mentale. Plus encore, les transformations que provoquent les stratégies et tactiques masculinistes sur la communauté féministe font émerger d'importantes questions à propos de la sécurité des femmes victimes de violences masculines. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Contremouvement, antiféminisme, masculinisme, féminisme, violence.
Keywords: IREF; amériques; antiféminisme; approches et analyses; discipline; mouvements féministes; mémoires/thèses; québec; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; violences

The Routledge handbook of gender and violence - Lombard, Nancy (Routledge handbooks, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Disentangling and locating the ''Global Right'': Anti-gender campaigns in Europe - Paternotte, David; Kuhar, Roman (Politics and Governance, 2018)
This article examines the development of campaigns against “gender ideology” in Europe, leading to the emergence of a specific family of mobilizations that we call anti-gender campaigns. These campaigns, started in the mid-1990s as a Catholic project in reaction to the results of the UN conferences of Cairo and Bejing, but developed significantly in several European countries after crucial encounters with right-wing populism. While recognizing the importance of these crossovers, we contend the interpretation that mobilizations against “gender ideology” and right-wing populism are the two faces of the same coin, and we plead for a more complex understanding of the ways in which distinct—and sometimes competing—projects can converge in specific settings. We argue that research on the “Global Right Wing” should therefore disentangle the various components of this phenomenon, and locate them in concrete settings. We show that this research strategy allows us to better grasp the specificities of each project and the ways in which they interact. Opening our eyes on crucial developments in contemporary Europe, this strategy also prevents researchers from falling into the trap of a global and unqualified backlash against everything achieved in terms of gender and sexuality in the last decades.
Keywords: discipline; europe; mouvements anti-genre; régions géographiques; sciences humaines; sociologie; thématiques; violences